IBM CICS and Liberty : what you need to know - Cunico, Hernan (IBM redbooks., 2016)
This IBM® Redbooks® publication, intended for architects, application developers, and system programmers, describes how to design and implement Java web-based applications in an IBM CICS® Liberty JVM server. This book is based on IBM CICS Transaction Server V5.3 (CICS TS) using the embedded IBM WebSphere® Application Server Liberty V8.5.5 technology. Liberty is an asset to your organization, whether you intend to extend existing enterprise services hosted in CICS, or develop new web-based applications supporting new lines of business. Fundamentally, Liberty is a composable, dynamic profile of IBM WebSphere Application Server that enables you to provision Java EE technology on a feature-by-feature basis. Liberty can be provisioned with as little as the HTTP transport and a servlet web container, or with the entire Java EE 6 Web Profile feature set depending on your application requirements. This publication includes a Technology Essentials section for architects and application developers to help understand the underlying technology, an Up-and-Running section for system programmers implementing the Liberty JVM server for the first time, and a set of real-life application development scenarios.